Antioxidant and Antityrosinase Activities of Ethanolic Pachyrhizuserosus Peel and Tuber Extract - Siregar, Irma Dolsyeria; Kusuma, Hanna Sari Widya; Widowati, Wahyu; Marpaung, Hans Hotma; Ferdinand, Sahna; Fachrial, Edy; Lister, I Nyoman Ehrich (Majalah Kedokteran Bandung, 2019)
Aging process is a physiological process in living organisms caused by, among others, free radicals. One of the free-radical-related aging problems is skin hyperpigmentation (excessive melanin) due to increasing tyrosinase enzyme activities. Natural compounds are widely used as antioxidant and antiaging agents. Bengkuang (Pachyrhizuserosus) is known as a source of various active compounds which can be used against free radicals to reduce the risk of skin aging through tyrosinase enzyme inhibition. This study was performed in September 2018 in Aretha Medika Utama, Biomolecular and Biomedical Research Center, Bandung, Indonesia to examine the antioxidant and antityrosinase properties of Pachyrhizuserosus peel extract (PPE) and Pachyrhizuserosus tuber extract (PTE).The extraction of PPE and PTE was performed using 70% ethanol by maceration method, followed by phytochemical analysis using modified Farnsworth method. Antioxidant activities were measured through 2,2-Diphenyl-1-picrylhydrazil (DPPH) scavenging activities while antiaging assay were conducted through the tyrosinase activity inhibition. In this study, PPE contained saponin, tannin, triterpenoid, and terpenoid while the PTE showed the presence of flavonoid, saponin, phenol, tannin, and alkaloid in phytochemical analysis. In the antioxidant assay, PPE presented a higher DPPH scavenging activities (IC50= 84.09 µg/mL) when compared to PTE (IC50= 98.30 µg/mL)(p<0.05). In antiaging assay, PPE showed a higher tyrosinase inhibitory activities when compared to PTE with =97.05µg/mL and 194.51µg/mL,respectively. It can be concluded that PPE has antioxidant and antiaging activities effective for preventing skin aging. Aktivitas Antioksidan dan Antitirosinase Ekstrak Etanol Kulit dan Daging Pachyrhizuserosus Proses penuaan merupakan suatu proses fisiologis yang terjadi pada makhluk hidup yang dapat disebabkan oleh radikal bebas. Hiperpigmentasi kuli tmerupakan salah satu masalah penuaan yang disebabkan oleh radikal bebas melalui peningkatan aktivitas enzim tirosinase. Bengkuang (Pachyrhizus erosus) diketahui mengandung berbagai senyawa aktif yang dapat menangkal radikal bebas serta mengurangi risiko penuaan kulit. Penelitian dilaksanakan pada September 2018 di Aretha Medika Utama, Biomolecular and Biomedical Research Center, Bandung, Indonesia untuk menguji kemampuan aktivitas antioksidan dan antitirosinase pada ekstrak etanol kulit bengkuang (EEKB) dan ekstrak etanol daging bengkuang (EEDB). Pembuatan ekstrak kulit dan daging bengkuang dilakukan dengan cara mengekstraksi bahan dengan etanol 70% menggunakan metode maserasi, kemudian dilanjutkan dengan analisis fitokimia ekstrak dengan modifikasi metode Farnsworth. Aktivitas antioksidan diuji dengan mengukur pemerangkapan 2,2-Diphenyl-1-picrylhydrazil (DPPH) sedangkan antiaging diuji dengan mengukur aktivitas penghambatan tirosinase. Pada uji fitokimia menunjukkan EEKB memiliki kandungan senyawa saponin, tanin, triterpenoid dan terpenoid, sedangkan EEDB menunjukkan kandungan senyawa flavonoid, saponin, fenol, tanin, dan alkaloid. Pada uji antioksidan, EEKB memiliki aktivitas tertinggi pada pemerangkapan DPPH (IC50=84.09 µg/mL) dibanding dengan EEDB (IC50=98.30 µg/mL) (pâ‰¤0.05). Pada pengujian antiaging, EEKB memiliki nilai yang lebih tinggi pada aktivitas penghambatan tirosinase dibandingkan dengan EEDB (IC50=97.05 µg/mL; 194.51 µg/mL (pâ‰¤0.05). Simpulan, EEKB memiliki aktivitas antioksidan dan antiaging sehingga efektif dalam mencegah penuaan kulit.